2019
DOI: 10.1371/journal.pgen.1008130
|View full text |Cite
|
Sign up to set email alerts
|

Variants in myelin regulatory factor (MYRF) cause autosomal dominant and syndromic nanophthalmos in humans and retinal degeneration in mice

Abstract: Nanophthalmos is a rare, potentially devastating eye condition characterized by small eyes with relatively normal anatomy, a high hyperopic refractive error, and frequent association with angle closure glaucoma and vision loss. The condition constitutes the extreme of hyperopia or farsightedness, a common refractive error that is associated with strabismus and amblyopia in children. NNO1 was the first mapped nanophthalmos locus. We used combined pooled exome sequencing and strong linkage data in the large fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
104
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(118 citation statements)
references
References 99 publications
12
104
0
2
Order By: Relevance
“…Chorioretinal folds, and/or choroidal effusions or retinal detachments were documented in 2/4 PRSS56 pedigrees and 1/3 MFRP pedigrees, with extra‐ocular features (in the form of dextrocardia or congenital diaphragmatic hernia) only observed in 3/5 members of the MYRF pedigree (Table S1). Within tissues of cadaveric human eyes, expression of the dominant genes MYRF and TMEM98 were more similar to one another, and higher, than the recessive genes MFRP and PRSS56 (Figure C), consistent with the known regulation of TMEM98 expression by MYRF . Also notable was the relatively high expression of PRSS56 in retina, where it is known to be derived from late retinal progenitor cells or Müller glia to promote elongation of ocular axial length both before and after eye opening .…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Chorioretinal folds, and/or choroidal effusions or retinal detachments were documented in 2/4 PRSS56 pedigrees and 1/3 MFRP pedigrees, with extra‐ocular features (in the form of dextrocardia or congenital diaphragmatic hernia) only observed in 3/5 members of the MYRF pedigree (Table S1). Within tissues of cadaveric human eyes, expression of the dominant genes MYRF and TMEM98 were more similar to one another, and higher, than the recessive genes MFRP and PRSS56 (Figure C), consistent with the known regulation of TMEM98 expression by MYRF . Also notable was the relatively high expression of PRSS56 in retina, where it is known to be derived from late retinal progenitor cells or Müller glia to promote elongation of ocular axial length both before and after eye opening .…”
Section: Resultssupporting
confidence: 63%
“…Posterior microphthalmos and nanophthalmos can be allelic, suggesting both conditions may represent a continuum of the same phenotypic spectrum . Most cases are explained by biallelic variants in MFRP and PRSS56 , with rare examples of monoallelic variants in TMEM98 and MYRF . PRSS56 and TMEM98 variants have since been implicated in multiple independent genome‐wide association studies of myopia …”
Section: Introductionmentioning
confidence: 99%
“…Truncating variants in MYRF were described in patients with genital anomalies (Hamanaka et al, 2019). In addition, loss of function variants in MYRF been described in patients with high hyperopia and nanophthalmos (Garnai et al, 2019;Xiao et al, 2019). (Kennerknecht et al, 1993;Sorgo et al, 1991).…”
mentioning
confidence: 99%
“…However, three recently published papers (Garnai et al, ; Guo et al, ; Xiao et al, ) independently identified that novel truncation mutations in MYRF are responsible for a spectrum of disorders related to autosomal dominant high hyperopia (adHH) (Nowilaty et al, ). These findings are of great interest because primary angle closure glaucoma (PACG), one of the most common forms of glaucoma in East Asians (Sun et al, ), is frequently accompanied with MYRF ‐associated high hyperopia (Garnai et al, ; Othman et al, ; Xiao et al, ). PACG or occludable anterior chamber angles, present in 12 of the 22 individuals with high hyperopia in one family (Othman et al, ), were caused by a MYRF mutation.…”
mentioning
confidence: 99%
“…Neither high hyperopia nor PACG have been reported in patients with CUDL disorders caused by MYRF mutations (Rossetti et al, ). However, ocular phenotypes cannot be excluded in these patients because one patient with an N‐terminal truncation mutation was reported to have adHH accompanied with systemic phenotypes which was consistent with CUDL disorders at the age of 8 years old (Garnai et al, ). The reason that neither adHH nor PACG were mentioned in other patients with MYRF ‐related CUDL disorders might be that they were obscured by CUDL disorders that were at the severe end of the spectrum.…”
mentioning
confidence: 99%